2023
DOI: 10.33160/yam.2023.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Micall2 Is Responsible for the Malignancy of Clear Cell Renal Cell Carcinoma

Abstract: Background There lacks a sufficient research on the tumorigenesis of clear cell renal cell carcinoma (ccRCC), causing that the prognosis of ccRCC was not effectively improved. Micall2 contributes to the malignancy of cancer. Moreover, Micall2 is considered a typical cell mobility-promoting factor. However, the relationship between Micall2 and ccRCC malignancy is unknown. Methods In this study, we first investigated the expression patterns of Micall2 in ccRCC tissues and cell lines. Next, we explored the in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Moreover, in vivo experiments have revealed that an increased expression of MICALL2 contributes to tumor growth and expansion. Similar to the others listed so far, it can therefore be considered a new prognostic marker and a potential therapeutic target [ 146 ].…”
Section: Novel Strategiesmentioning
confidence: 94%
“…Moreover, in vivo experiments have revealed that an increased expression of MICALL2 contributes to tumor growth and expansion. Similar to the others listed so far, it can therefore be considered a new prognostic marker and a potential therapeutic target [ 146 ].…”
Section: Novel Strategiesmentioning
confidence: 94%